PENERAPAN MODEL COOPERATIVE LEARNING METODE THINK PARE SHARE SEBAGAI UPAYA PENINGKATAN PRESTASI MATA KULIAH EKONOMI MONETER - Ninik Srijani (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2013)
This study aims to improve  the academic  achievement   of monetary  Economics course  through  Cooperative   Learning  Model  Type TPS  ( Think  - Pair - Share)   on Economic  Education  students.  The subjects  in this study were students who take courses Monetary   Economics  Odd Semester  2012/2013.  Number  of students  31 data coUection by observation  techniques  and evaluation  of learning outcomes,  and then ana Iyzed with a formula  to determine   the percentage   increase  in each  cycle,  while  dle action  research procedures  through  2 cycles and each cycle consisted  of 4 series of activities  carried  out are 1 ) Planning;  2 ) Implementation;   3 ) Observation,  and 4)  Reflection.  Method  of data collection  is done by using the observation  and evaluation  of learning.  Observations  are used  to determine   the activity  of students  in the  learning  process  by using  a model  of Cooperative  Type TPS (Think  - Pair - Share ). while the evaluation  is used to determine the achievement  of monetary economics  courses The results of the observation  and evalu- ation  of student  learning  outcomes   Prodi  Economic  Education   bas  increased.  This  is indicated  by the observation  of the lndidvidu   active students  in the learning  process  bas increased,   where  the  interest  and  attention  of  students  to  the  material  presented  first cycle of the original  61.29% to 83.87%,  tbe activity  asks students  in the first cycle of the original 54,  84%  to 71 %, active students and issue an opinion in response to the first cycle of the  original 48.39%   to 62.29%,   level of student discipline  in the process of learning to learn in the first cycle the original 64.52%  to 80.64%. Being in a group activ- ity of students in the learning process has increased, where the interest and attention of students  to the first cycle of the material presented  is original 51.61%  to 74.19%,  the activity asks students in the first cycle of the original 48.39%  to 64,52%,   active students and issue an opinion in response to the first cycle of the original 48.39%  to 74.19%,  level of student discipline  in the process of learning to learn in the first cycle the original 64.74%  to 83.87%.  For evaluation of learning in the first cycle masiswa the above aver-age learning  initially increased to 64.74%  83.87%  students below average dropped to 32.26%  16.31. Based on the research results of the second cycle, it can be concluded that the model learning SMT Type Cooperative  ( Think - Pair  - Share)   can improve the learning achievement of Monetary Economics courses.